Stable Expression of Green Fluorescent Protein after Liposomal Transfection of K562 Cells without Selective Growth Conditions. (December 1999) - Gubin, A.N.; Koduru, S.; Njoroge, J.M.; Bhatnagar, R.; Miller, J.L.
Little is known about the durability of plasmid DNA transgene expression in mammalian cells in the absence of growth selection. For this purpose, we have begun the study of liposomal transfer and expression of plasmid DNA encoding green fluorescent protein (GFP) in human erythroleukemia K562 cells. Detection and selection of GFP expression were accomplished visually and by flow cytometry. GFP expression was noticeable in cells within 4 h of transfection. In nine separate transfections, approximately 20% of the transfected cells expressed GFP with a mean fluorescence 40–50× that of control cells (15 fluorescent units [FU] vs. 0.3 FU) during the first five days after transfection. The percentage of GFP positive cells dropped rapidly to 0.1% by day 14 post-transfection, but fluorescence activated cell sorting on this day resulted in the identification of stable transfectants expressing GFP for an additional 6–12 months in culture. GFP expression is adequate for the identification, isolation and monitoring of stable transfection events after lipid-mediated transfection of eukaryotic cells.